The relationship between organizational commitment and turnover intention among employees at a manufacturing company in Malaysia - Ling, G. J. (International Information Institute Ltd., 2016)
Retaining employees is an important task to all organization. Therefore, turnover should be reduced as it caused high cost on the company. In order to reduce the turnover rate, the turnover intention of the employees should be known because it is the predictor of the actual turnover action. Organizational commitment is viewed as one of the important factors to retain employees in organization. Thus, the main purpose of this study is to determine the relationship between organizational commitment and turnover intention among 127 employees in a manufacturing company in Malaysia. The Statistical Package for Social Science (SPSS) version 20.0 was used to analyze the data. The findings show moderate level of employees' commitments and turnover intention. Meanwhile, the correlation between employees' organizational commitment and turnover intention is found to be negative and strong with significant relationship with r = -0.921. In short, an empirical investigation was conducted to study the relationship between employees' organizational commitment and turnover intention in a Malaysian manufacturing company. The results showed that there are negative as well as significant relationships between affective commitment, continuance commitment, normative commitment, and turnover intention.